FINANCIAL RISK MANAGEMENT IN DEBT COLLECTION COMPANIES: EXAMINING STRATEGIES FOR CREDIT RECOVERY AND LOSS MINIMIZATION - Neves Filho, Alexandre Wagner Barbosa (Revista Sistemática, 2020)
This article examines financial risk management strategies in debt collection companies, emphasizing the dual necessity of maximizing credit recovery and minimizing financial losses. Drawing on credit risk modeling, portfolio segmentation, operational controls, and regulatory compliance, the discussion highlights how predictive analytics, tiered recovery strategies, and technology-driven tools contribute to effective decision-making. The study also considers the role of human capital, organizational culture, and stress testing in strengthening resilience against macroeconomic shocks. By integrating data-driven methods with ethical and compliant practices, debt collection firms can enhance financial stability, optimize recovery processes, and reduce exposure to legal and reputational risks.